Social Spending for Inclusive Growth in the Middle East and Central Asia - Mathai, Koshy (Departmental Papers; Departmental Paper ;, 2020)
This paper examines the role of social spending in improving socioeconomic outcomes in the Middle East and Central Asia. In particular, it addresses the following questions: (1) how large is social spending across the region? (2) how do countries in the region fare on socioeconomic outcomes? (3) how important is social spending as a determinant of these outcomes? and (4) how efficient is social spending in the region?